What drives the disappearing dividends phenomenon? - Kuo, Jing-Ming; Philip, Dennis; Zhang, Qingjing (Journal of Banking & Finance, 2013)
We study the determinants of dividend payout policy and examine the role of liquidity, risk and catering in explaining the changes in propensity to pay. Our results indicate that risk plays a major role in firms’ dividend policy. The evidence substantiates from a large sample of firms representing 18 countries over the sample period from 1989 to 2011. For firms in the US, France, UK and Other European markets, liquidity is additionally an important determinant of dividend policy. We find that, although catering incentives persist only among firms in common law countries and not in civil law countries, after adjusting for risk there is little support for catering theory even among firms incorporated in common law countries. Our results indicate that catering incentives reflect the risk-reward relationship in the changing propensity to pay dividends.